Seismic risk management of piles in liquefiable soils stabilised with cementation or lattice structures. Issue 2 (14th September 2018) - Rostami, Rohollah; Bhattacharya, Subhamoy; Hytiris, Nicholas; Mickovski, Slobodan B
Abstract : Liquefaction is an important seismic hazard that can cause extensive damage and high economic impact during earthquakes. Despite the extensive research, methodologies and approaches for managing liquefaction for pile-supported structures, failures of structures due to liquefaction have continued to occur to this day. The main aim of this paper is to develop a simplified methodology for reducing potential structural damage of structures founded in soils susceptible to liquefaction. In order to implement a successful remediation technique, the current methods for pile failure in liquefiable soils and remediation schemes of earthquake-induced liquefaction are critically reviewed and discussed. Cementation and lattice structure techniques for reducing liquefaction hazard are proposed, while numerical analysis for unimproved and stabilised soil profiles using the finite-element method is carried out to simulate the analysis of both stabilisation techniques. The results showed that both techniques are effective and economically viable for reduction or avoidance of potential structural damage caused by liquefied soil and can be used in isolation or in combination, depending on the ground profile and pile type.